Ice core evidence for the Los Chocoyos supereruption disputes millennial-scale climate impact - Helen M. Innes; William Hutchison; Michael Sigl; Laura Crick; Peter M. Abbott; Matthias Bigler; Nathan J. Chellman; Siwan M. Davies; Steffen Kutterolf; Joseph R. McConnell; Mirko Severi; R. Stephen J. Sparks; et al. (Communications Earth & Environment)
Abstract Volcanic supereruptions are considered among the few drivers of global and existential catastrophes, with recent hypotheses suggesting massive volcanic stratospheric sulfate injection could instigate major shifts in global climate. The absence of supereruptions during recent history as well as large uncertainties on eruption ages limits understanding of the climatic risk they impose. Polar ice cores have well-resolved continuous age models, record past temperature, and contain volcanic sulfate and cryptotephra deposits which can be geochemically fingerprinted to determine eruption timing and improve stratospheric sulfur loading estimates. Here, we provide an age of 79,500 years for the Atitlán Los Chocoyos supereruption, one of the largest Quaternary eruptions, by identifying tephra shards in ice cores from both Greenland and Antarctica. This ice core age is supported by a revised marine sediment core stratigraphy age for the Los Chocoyos ash layer. Through comparison with well-dated ice-core temperature proxy records, our study suggests that despite being one of the largest sulfur emissions recorded in ice cores, the Los Chocoyos supereruption did not trigger a millennial-scale cold period.